Selective adsorption of phenanthrene dissolved in Tween 80 solution using activated carbon derived from walnut shells. (October 2018) - Zheng, Xin; Lin, Heng; Tao, Yufang; Zhang, Hui
Abstract: In order to remove phenanthrene (PHE) from surfactant solution, activated carbon (AC) was prepared from waste walnut shells and characterized by Brunauer-Emmett-Teller (BET), field-emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). For solutions containing PHE and Tween 80, the former was effectively removed and the latter could be economically recovered after adsorption by the prepared AC. The π-π interactions and oxygen containing functional groups of AC play important roles in the PHE adsorption process. The adsorption kinetics process could best be described using the pseudo-second-order model and adsorption isotherm results indicated that the Langmuir model best fitted the data. Adsorption thermodynamic parameters, including enthalpy change, Gibbs free energy change and entropy change were calculated. Under optimal conditions, PHE removal and Tween 80 recovery reached 95% and 90%, respectively. The results suggest that AC provided an efficient alternative for selective adsorption of PHE and recovery of Tween 80 after the soil washing processes. After adsorption AC could be regenerated with ethanol and even if AC were regenerated twice PHE removal reached 80%. Graphical abstract: Image 1 Highlights: AC was prepared from walnut shell to adsorb phenanthrene from Tween 80 solution. 247.54 mg g −1 adsorption capacity, 95% phenanthrene removal and 90% Tween 80 recovery. π-π interactions and oxygen containing groups play important roles in adsorption. The activated carbon could be regenerated and reused at least two times.